Customizing the Therapeutic Response of Signaling Networks to Promote Antitumor Responses by Drug Combinations - Goltsov, Alexey; Langdon, Simon; Goltsov, Gregory; Harrison, David; Bown, James (Frontiers in Oncology, 2014)
Drug resistance, de novo and acquired, pervades cellular signalling networks from one signalling motif to another as a result of cancer progression and/or drug intervention. This resistance is one of the key determinants of efficacy in targeted anticancer drug therapy. Although poorly understood, drug resistance is already being addressed in combination therapy by selecting drug targets where sensitivity increases due to combination components or as a result of de novo or acquired mutations. Additionally, successive drug combinations have shown low resistance potency. To promote a rational, systematic development of combination therapies, it is necessary to establish the underlying mechanisms that drive the advantages of drug combinations and design methods to determine advanced targets for drug combination therapy. Based on a joint systems analysis of cellular signalling network (SN) response and its sensitivity to drug action and oncogenic mutations, we describe an in silico method to analyse the targets of drug combinations. The method explores mechanisms of sensitizing the SN through combination of two drugs targeting vertical signalling pathways. We propose a paradigm of SN response customization by one drug to both maximize the effect of another drug in combination and promote a robust therapeutic response against oncogenic mutations. The method was applied to the customization of the response of the ErbB/PI3K/PTEN/AKT pathway by combination of drugs targeting HER2 receptors and proteins in the downstream pathway. The results of a computational experiment showed that the modification of the SN response from hyperbolic to smooth sigmoid response by manipulation of two drugs in combination leads to greater robustness in therapeutic response against oncogenic mutations determining cancer heterogeneity. The application of this method in drug combination co-development suggests a combined evaluation of inhibition effects along with the capability of drug combinat